An office design and employee stress : an office design that reduces employee’s stress and increases employee productivity - Papierska, Alicja (2018)
We live in times when office space is playing a key role in company and employees' life. Employees productivity is a fundamental element of any businesses' success nowadays. A competitive global environment determines this phenomenon. Workers productivity can be remarkably reduced by high level of stress and poor quality of interior. Both stress and bad working conditions have an influence on employees’ well-being. In addition, they can result in pain and health problems, which as a result can reduce the willingness to work. The main aim of this study was to explore interior design techniques, which can reduce employees’ stress and at the same time increase their productivity. For this purpose, an action-research project was made. The project is composed of a design proposal for an interior design company in Poland. The design solution is based on Biopfilic Design with some elements of Activity Based Working. Biophlic design is a trend in interior design that emphasizes contact with nature. By using this design techniques (plants introduction, sunlight, nice window view for the greenery), it is possible to make workers feel better and at the same time to make them more creative and productive. The role of the Activity Based Working assumption is to match the workplace to the needs of employee. The private and open space, creative room, meeting room, dining room, gym, sauna are designed according to Activity Based Working. Common space is designed to increase collaboration among employee and to reduce the work stress. Ergonomic furniture and introduction of plants are the elements which increase productivity and protect health of both employees and customers. To understand the space and employees’ needs better a questionnaire was made. Using primary data, taking into consideration employees' answers and employers expectations a functional layout was designed. Before doing a design, many books and articles were read to understand an office design subject well. The best office design examples, which came into existence in Poland, were studied and carefully analyzed. Getting acquainted with office projects designed by the best architects was a necessary study which inspired me to continue a design work for Kolanko Company. Two-storey building with specious stockroom was built in Chwaszczyno in Poland. The new building of the company is dedicated to individual customer and architects who want to collaborate with Kolanko Company. New headquarters of Kolanko company may help clients enjoy a better service. Thanks to the showroom clients will be able to see a product before the purchase which makes their choice more conscious. An installation, products exhibitions can facilitate the client’s choice as well as inspire them. The modern office is a mix of twenty years of experience with new technologies in interior design area. The main purpose of new office is to provide the best condition for employee’s well-being and client’s service. There are many studies, which present the influence of office design on workers’ stress and productivity. Poor design can dramatically reduce employee productivity and may contribute to many health problems. There are some design techniques, which can improve work, information flow in an office and well-being of employees. In the project of Kolanko headquarters, office furniture, textures, colors and light, were carefully selected to ensure better working conditions. There are some elements called positive distraction in the project (gym, sauna, dinning area, creative room) that have an impact on reducing stress during work. Plants and the window view have possitive influence on state of being and people's creativity